2016
DOI: 10.24093/awej/vol7no4.24
|View full text |Cite
|
Sign up to set email alerts
|

EFL_ Indonesian Students’ Attitude toward Writing in English

Abstract: Writing is a sophisticated language skill since it requires the ability not only to tailor ideas, but also to construct acceptable sentences to create a meaningful, logical, and comprehensible work. As a result, English as a Foreign Language (EFL) learners have to maximize their efforts to put their thoughts on the paper. This paper is intended to describe the EFL students attitude toward writing. There were 57 students participating in the study. The data was collected by using questionnaire, interview, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 8 publications
1
21
0
2
Order By: Relevance
“…Megaiab's study (2014) found out that the students' native language influence the text quality of their composition because of their lack competence in grammar and writing elements. Because of its complexity, many EFL students have negative attitude toward writing because they view writing as "difficult and stressful" (Setyowati & Sukmawan, 2016). For Cahyono (2009), the students' view of writing difficulty might lay in their perception on the use of correct grammar and vocabulary when the ideas are translated in the text.…”
Section: Volume 5 Issue 3 September 2017mentioning
confidence: 99%
See 3 more Smart Citations
“…Megaiab's study (2014) found out that the students' native language influence the text quality of their composition because of their lack competence in grammar and writing elements. Because of its complexity, many EFL students have negative attitude toward writing because they view writing as "difficult and stressful" (Setyowati & Sukmawan, 2016). For Cahyono (2009), the students' view of writing difficulty might lay in their perception on the use of correct grammar and vocabulary when the ideas are translated in the text.…”
Section: Volume 5 Issue 3 September 2017mentioning
confidence: 99%
“…In Indonesian context where English is taught as a foreign language, among other skills, writing becomes the most difficult skill to master (Cahyono, 2009;Setyowati &Sukmawan, 2016). It is all because writing is more than just outputting the accurate sentences and paragraphs (Hedge, 2005).…”
Section: Volume 5 Issue 3 September 2017mentioning
confidence: 99%
See 2 more Smart Citations
“…Results of an interview stated by Setyowati & Sukmawan (2016) also reveal that although students have moderate attitudes towards writing, they perceive writing as difficult, and stressful. While those with high attitudes, mostly views writing as interesting and challenging.…”
Section: Introductionmentioning
confidence: 97%